Sistem Monitoring Praktik Kerja Lapangan Berbasis Web di SMK Negeri 1 Suwawa - Sri Yayunda Adjun; Sitti Suhada; Mohamad Syafri Tuloli (Gorontalo State University, 2021)
Field practice program for SMK Negeri 1 Suwawa remains to contain obstacle particularly related to is difficulty in monitoring student's activity during the program in a predetermined location. Students who fill out their attendance list on their own may lead to dishonesty by falsifying their presence through compromising it with other students who attend in the field practice location. Objective of this research was to develop a web-based field practice monitoring system at SMK Negeri 1 Suwawa to facilitate person in charge and teacher as advisor of field practice. A system development method used in this research was Waterfall by applying PHP programming language and MySQL database. Result of this research indicated that the system developed could assist both the person in charge and the advisor of field practice in monitoring daily activity and attendance of students in the location of program. In addition, the student's attendance registration was performed by office advisor so that the students could not fake it. Therefore, the system has made information access to the field practice easier.